Land, Memory, Reconstruction, and Justice: Perspectives on Land Claims in South Africa - Walker, Cherryl (Ohio University Press, 2010)
Land is a significant and controversial topic in South Africa. Addressing the land claims of those dispossessed in the past has proved to be a demanding, multidimensional process. In many respects the land restitution program that was launched as part of the county's transition to democracy in 1994 has failed to meet expectations, with ordinary citizens, policymakers, and analysts questioning not only its progress but also its outcomes and parameters.Land, Memory, Reconstruction, and Justicebrings together a wealth of topical material and case studies by leading experts in the field who present a rich mix of perspectives from politics, sociology, geography, social anthropology, law, history, and agricultural economics. The collection addresses both the material and the symbolic dimensions of land claims, in rural and urban contexts, and explores the complex intersection of issues confronting the restitution program, from the promotion of livelihoods to questions of rights, identity, and transitional justice.A valuable contribution to the field of land and agrarian studies, both in South Africa and internationally, it is undoubtedly the most comprehensive treatment to date of South Africa's postapartheid land claims process and will be essential reading for scholars and students of land reform for years to come.